Multiple Directorships And Financial Performance Of Malaysian Public Listed Firms: Do Roles And Dedication Of Directors Matter? - Lok Char, Lee (2019)
Motivated by the inconclusive evidence on multiple directorships and a close look at the literature reveals that the concern about multiple directorships is not necessarily about the number of board seats of individual directors. This study examines the characteristics of the directors having multiple directorships and the effects on firm performance using a sample of 4,964 observations from non-financial firms listed on the main market of the Bursa Malaysia from 2009 to 2015.